Pengembangan Media Video Animasi Tematik Tema 4 Kewajiban dan Hakku Untuk Siswa Kelas III Sekolah Dasar - Amalia, Mersi; Ramadan, Zaka Hadikusuma (Jayapangus Press, 2024)
Learning media is an important tool in the learning process which functions to achieve learning goals. The lack of availability of interesting learning media in elementary schools causes learning to become monotonous. This research aims to determine the process of developing animated video media and the validity of animated video media. This research method is development research using the 4D model, namely define, design, development and dissemination. The resulting learning media is animated video media for theme 4, my obligations and rights, subtheme 1, my obligations and rights, learning 1. The validity of animated video media received a very valid category without revision, reviewed based on validation results by material experts, language experts and design experts. In the material aspect, the average score was 94.56% in the very valid category, in the language aspect, the average score was 93.33% in the very valid category, and in the design aspect, the average score was 100% in the very valid category.